Redes Colectivas Baseadas em Competencias: O Caso da ACECIA, ACE - Garrett, Alexandre Ferreira Cabral de Almeida (2006)
Cooperation in industrial network is one of the most studied phenomenons in the network approach developed by the IMP Group (Industrial Marketing and Purchasing). In this theoretical field there are models that study collective cooperation which explain the formation of issue-based nets groups of actors that through cooperation try to cope collectively with a common issue or problem. This dissertation is divided in two areas. The first part is dedicated to explain how a collective actor is able to solve a positioning problem of actors involved. The collective action model is enriched with some of the concepts developed by the capabilities approach. The second purpose of this dissertation is to develop a more dynamic perspective of the issue-based net, seeking to explain how the collective actor develops trough time in order to fulfil its objectives. In conclusion, the analytic model presented in this dissertation, being an extension of the business network literature, explains the motifs, the conditions and the process used by which issue-based nets coordinate activities.